The effect of different citric acid concentration on physicochemical and antioxidant properties of Red Pitaya peel gummy candies - Mohsin, Aliah Zannierah; Mohd Maidin, Nurmahani; Mohd Isa, Nur Suaidah; Cheok, Hui Yun (University of Benin, 2025)
Red pitaya peels (RPP), often discarded as waste, are rich in betacyanin, making them a potential natural colourant for food products such as gummy candy. However, citric acid may influence the quality and stability of the colourant. This study examined the physicochemical, antioxidant, and sensory properties of RPP gummy candies with different citric acid concentrations. The RPP were dehydrated, ground into powder, and incorporated into gummy formulations. Citric acid significantly reduced water activity (p<0.05), lowered pH, and increased titratable acidity. Colour analysis showed a significant rise (p<0.05) in a* value with higher citric acid, indicating a redder colour. Samples containing 3% citric acid exhibited a marked reduction (p<0.05) in chewiness. Antioxidant properties were also affected, with the 3% citric acid sample showing the highest total phenolic content (0.91 mg GAE/g) and DPPH radical scavenging activity (40.73%). However, total betacyanin content declined significantly (p<0.05) in samples with citric acid, ranging from 0.55-0.85 mg/g, compared to 1.79 mg/g with 0% citric acid. Sensory evaluation revealed that the 2% citric acid sample received the highest scores for most attributes, suggesting an optimal balance between flavour and texture. Overall, the study highlights the potential of RPP as a natural colourant and demonstrates how varying citric acid concentrations impact the physical, antioxidant, and sensory qualities of gummy candy. These findings underscore the importance of optimising citric acid levels to maintain both the functional and sensory attributes of RPP-infused gummy candies.